Perception of COVID-19 Testing in the Entire Population - Gavurova, Beata; Ivankova, Viera; Rigelsky, Martin; Caha, Zdenek; Mudarri, Tawfik (Frontiers in Public Health, 2022)
In the Slovak Republic, a mass testing of the entire population was performed. Estimates show that this testing cost more than 400 million EUR and thousands of euros were paid for one positively identified case. Thus, it is possible to state a high cost for such a project, which has been criticized by many parties. On the other hand, from a public health point of view, mass testing has helped fight the pandemic. Both the health and economic perspectives are important in assessing the success of a pandemic strategy, but the social perspective is equally important. In fact, the situation is perceived from the position of public leaders who make decisions, but also from the position of the society that bears individual political decisions. It is not appropriate to forget about the society that is most affected by restrictions, testing, health status, but also the burden on the state budget. The objective of the presented research was to examine the perception of testing for coronavirus disease 2019 (COVID-19) in the Slovak population. Non-parametric difference tests and correspondence analysis were used for statistical processing. The research sample consisted of 806 respondents and data collection took place in February 2021. The main findings include significant differences in perceptions between the first and the last participation in testing in terms of gender, age, testing experience, and time aspect. The last participation in testing showed lower rates of positive aspects related to the internal motivation to test compared to the first participation. In contrast, external stimulation by government regulations related to restrictions in the absence of a negative result was higher in the last participation in testing. There were also differences between the first and the last test in the level of doubts about the accuracy of the test result, while a higher level was found at the last testing participation. It can be concluded that the frequency of testing and its requirements need to be approached very carefully over time, as it is likely that the positive perceptions may deteriorate. The recommendations include clear and timely government communication, trust building and health education.